Inflation, Debt, and Default in a Monetary Union - Jahjah, Samir (IMF Working Papers; Working Paper ;, 2000)
Depending on the preferences of the central bank, countries in a monetary union tend to accumulate less debt. This reduces the need for fiscal criteria such as debt ceilings. In a monetary union with an independent central bank and a sufficiently large number of relatively small members, investors will begin rationing credit to the government more rapidly, and an equilibrium with no inflation and no default exists. However, highly-indebted countries are more likely to default once they join a monetary union.